ENERWATER – A standard method for assessing and improving the energy efficiency of wastewater treatment plants. (15th May 2019) - Longo, S.; Mauricio-Iglesias, M.; Soares, A.; Campo, P.; Fatone, F.; Eusebi, A.L.; Akkersdijk, E.; Stefani, L.; Hospido, A.
Highlights: A novel standard methodology for WWTPs energy efficiency estimation is presented. The methodology is based on KPIs that reflect the plant function (s). The methodology allows benchmarking and diagnosing energy hotspots. A case study illustrates the procedure to carry out an energy analysis. Abstract: This paper describes the first methodology specifically tailored to estimate energy efficiency at wastewater treatment plants (WWTPs). Inspired by the cycle of continuous improvement, the method (i) precisely defines the concept of energy efficiency in WWTPs, (ii) proposes systematic and comparable ways to measure it, and (iii) allows benchmarking and diagnosing energy hotspots. The methodology delivers an aggregated measure of the WWTP energy efficiency defined as the Water Treatment Energy Index, a single energy label that uses universally known illustrations enabling wide communication of standardized information on the WWTP energy status. The accuracy, reproducibility and generality of the methodology were validated by a widespread energy benchmarking method, and a case study is presented to show its capabilities. By promoting dialogue towards the creation of a specific European Standard, the actions accomplished by the H2020 Coordination Support Action ENERWATER should positively contribute to improving the exchange of information on energy saving actions and results between wastewater utilities and towards other stakeholders.